Reproductive and lactation performance of Kenana and Butana crossbred cows, Gezira State, Sudan - Mudawi, Tilal M. A.; Abdalla, Hyder O.; Gasmalla, Tasabeeh E. M. (Gezira Journal of Agricultural Science, 2019)
Kenana and Butana cattle are the main indigenous dairy breeds in the Sudan. However, their productive performance is generally low compared to exotic breeds. This necessitates the crossbreeding with high milk producing breeds to meet the increasing demand for milk and dairy products through improving the genetic potential of the indigenous dairy cattle breeds. The objectives of this study were to determine the overall performance of Kenana and Butana 50% crosses with Friesian bulls, to estimate selected reproductive and lactation traits and to study the effects of dam breed, parity, lactation number, season and year of calving on those traits. A total number of 120 records for 30 dairy cows, each for four lactation seasons were used. Data were collected from the master records of Elbashaier dairy farm, about 10 km south of Wadmedani. They covered the years 1990- 2005. The overall means of crossbred dairy cows (days) for age at first calving, calving interval, open period, dry period and lactation period were 970, 400, 122, 65 and 332, respectively. Lactation, daily and standard yields (kg) were 3771, 12 and 3505, respectively. Kenana crossbred cows had higher calving interval, open, dry, lactation periods and lactation yield. Butana crossbred cows had higher age at first calving, daily and standard lactation yields. However, the effect of dam breed was not significant. Dam parity had significant effects (P≤0.05) on all traits except dry period. Age at first calving increased gradually while calving interval and lactation period decreased gradually with parity. Lactation yield was higher in the first and second parities, and daily and standard lactation yields were higher in the fourth parity. Lactation number had significant effects (P≤0.05) on all traits, except open period. Lactation period was higher in the first lactation, while dry period, lactation, daily and standard yields were least in the first lactation and increased with advanced lactation. Season of calving had significant effects (P≤0.05) on calving interval, open period, daily and standard lactation yields. Calving interval, open and lactation periods were longer, while, daily and standard lactation yields were lower during winter. Year of calving had significant effects (P≤0.05) on all traits except dry period. Age at first calving increased gradually with age.